Obstetric and neonatal outcome in multiple pregnancy in rural India: a prospective study - G., Lakshmikantha; C., Sangeetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective is to study the obstetric and perinatal outcome in multiple pregnancy. Methods: A prospective study of 100 cases of multiple pregnancy was conducted between October 2013 to July 2016. Incidence of relevant factors, complications, characteristic of multiple pregnancy and sequelae of these complications on obstetric and perinatal outcome were analyzed. Results: Incidence of multiple pregnancy was 2%, anaemia was 22%, preterm labour in 62%, severe preeclampsia in 34%, postpartum haemorrhage in 16%’ PPROM in 14%, abortion in 8%, eclampsia in 2%. Incidence of perinatal mortality rate was 240 per 1000 live births and maternal mortality rates was 2000/ 1 lakh live births which was 10 times more compared to singleton pregnancy. Conclusions: Regular antenatal care, prolonging period of gestation near to term, early admission and care will go a long way in reducing maternal and perinatal mortality.